Country Foods in Schools: Incorporating Student Preferences in the Inuvialuit Settlement Region, NWT - Sallans, Alissa (Université d'Ottawa | University of Ottawa, 2024)
Introduction: Food security across Inuit Nunangat is deeply tied to country foods. As fewer youth are spending time harvesting, preparing, and eating country foods than in previous generations, it becomes relevant to understand how to involve young people in their local food systems. In the Inuvialuit Settlement Region (ISR), schools provide one opportunity to support country food consumption and land-based learning as part of efforts to Indigenize education. Given limited research on student country food and activity preferences, this study aims to capture the current state of student preferences, interests, and experiences in the ISR. Objectives: The objectives of this study are to: (1) document student preferences for country foods and land-based activities, (2) understand student access to and preferences for learning about country foods, and (3) understand how schools are supporting student engagement with country foods and barriers to doing so. As such, this thesis aims to answer the research question: what are student perspectives regarding country foods in the ISR and how can schools foster student engagement with local food systems? Methods: This cross-sectional, mixed methods study design collected quantitative image-based survey data through purposive-convenience sampling from students in grades 1 to 12 from the seven schools across the Inuvialuit Settlement Region (ISR) between 2022 and 2023 (n=278). The aim was to capture community-level and regional similarities and differences in the country food preferences of students. Once the survey data was analyzed, qualitative methods were utilized to help ground the survey findings. To confirm the validity and reliability of survey results, talking circles with grade 6 to 12 students took place in three ISR communities (n=3). To further explore and elaborate on survey findings, semi-structured interviews were conducted with school food program administrators in five ISR communities (n=6). Findings: This research finds that perspectives captured through the student survey regarding country foods in the ISR are diverse and linked to local geographies and species distribution; however, there are commonalities across the region regarding the country foods that students prefer to eat, harvest, and prepare, with caribou being the most commonly preferred. Results also indicate that students have a high level of interest in country food activities, including fishing, berry picking, jiggling, making dry meat, and cooking. Students further expressed a strong desire to learn about country foods from their families. Talking circles and interviews confirmed and expanded upon the findings of the survey, by sharing personal and school experiences of harvesting and preparing country foods. Interview results highlight the experiential land-based opportunities that schools foster across the ISR which promote student engagement with country foods. This research finds that schools can foster student engagement with country foods through on-the-land activities, connecting curriculum with traditional knowledge, and through serving country foods in schools as part of coordinated school food programs. Conclusion: The results of this research provide a regional baseline against which student interests and preferences for country foods can be measured, an opportunity for schools and communities to continue engaging students in their local food system, and a model for conducting regional surveys with children and youth. This study encourages future research to consider how the voices and perspectives of children and youth can be incorporated into food security research, policy development, and program design.
Keywords: Country Food; Inuvialuit Settlement Region; Youth; Food Preference; School